Usury in the Light of the Qur'an in Contemporary Problems - Dini Kartika; Apriyanti, Apriyanti; Dwi Ririn Melia (Al-Shamela : Journal of Quranic and Hadith Studies, 2025)
This article aims to examine the verses of usury and its relation to human activities by making three lending applications namely Shopee PayLater, Smart Credit, and Savings and Loan Cooperative as research objects. These three applications are quite popular among the public so that many Muslims participate in them. This research is a qualitative research by applying the maudhu'i method. Primary data comes from verses of the Qur'an, while secondary data is taken from books and articles related to the research. All data will be analyzed with descriptive-analytical method that describes and interprets the object of research by containing facts in accordance with the actual situation. The results of the study found that usury confirmed in several verses of the Qur'an has five indicators, namely: First; there is an addition to the payment time, second; there is an addition to the payment, third; the exchange of unequal value of goods, fourth; there is an element of intimidation, and fifth; there are parties who benefit and parties who are harmed. These five indicators are not met in the Cooperative Savings and Loan application, but are indicated in Shopee PayLater and Smart Credit. The existence of these five indicators is expected to be able to help in filtering any form of economic activity of the Muslim community so as to avoid usury activities that are forbidden. This research contributes to helping filter any form of economic activity of the Muslim community so as to avoid usury activities that are forbidden by religion.